Resin film, circuit board material, circuit board and electronic apparatus
The resin film composition addresses high heat press temperature issues by controlling crystallization speed and adhesion, enabling efficient multi-layering at lower temperatures with improved mechanical and electrical properties.
Patent Information
- Application Number
- JP2023120017
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
Conventional resin films containing polyether ketone and polyimide require high heat press temperatures for multi-layering, leading to inefficiencies in processing and manufacturing due to issues like resin deformation and adhesion problems.
A resin film composition with specific properties, including a glass transition temperature range of 140-170°C, a crystallization temperature difference of 50-70°C, and controlled crystallization speed, allowing for lower heat press temperatures without adhesives, enhancing adhesion and processing efficiency.
The resin film enables multi-layering at reduced temperatures, improving processing efficiency, adhesion, and maintaining mechanical and electrical properties, while reducing resin deformation and signal loss.
Smart Images

Figure 2025017120000001 
Figure 2025017120000002 
Figure 2025017120000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin film, a circuit board material, a circuit board, and an electronic device. [Background technology]
[0002] In recent years, with the diversification of electronic devices, the materials of the circuit boards used in electronic devices have also become more diverse. For example, the most commonly used circuit board materials are copper-clad laminates (CCL), which are made by layering resin-impregnated sheets (prepregs) on base materials such as paper or glass, and applying copper foil to the surface of the insulating plate obtained by pressurizing and heating it, and flexible printed circuit boards (FPC), which are made by forming an insulating adhesive layer on a base film and then laminating a conductive foil such as copper on top of that.
[0003] Insulating materials for circuit boards are required to have solder reflow heat resistance in the manufacturing process. For example, if heat-resistant thermoplastic resins such as polyether ketone resins and polyimide resins can be used as insulating materials for printed wiring boards, it is expected that they will have excellent electrical properties at high temperatures and will provide reliable circuits in high-temperature environments. However, these heat-resistant thermoplastic resins have high molding temperatures, so when they are bonded to copper foil or made into multi-layer boards, they need to be molded at high temperatures under hot press molding at a molten state of 260°C or higher, which causes problems such as long heating and cooling times. Furthermore, in the case of crystalline resins, they cannot be adhesive unless they are heated to a temperature close to their melting point, and when the melting point is exceeded, the resin flows out and becomes deformed.
[0004] Also, the use of polyetheretherketone (PEEK) resin, known as a super engineering plastic, as an insulating material for circuit boards is being considered. Polyetheretherketone (PEEK) resin is a highly functional thermoplastic resin, and is excellent in heat resistance, high temperature characteristics, hydrolysis resistance, mechanical strength, flame retardancy, chemical resistance, electrical characteristics, etc. For example, Patent Document 1 discloses a film obtained by mixing 20 parts by weight or more and less than 50 parts by weight of scale-like inorganic particles with 100 parts by weight of thermoplastic resin, and discloses the use of polyetheretherketone resin (PEEK) and polyetherimide resin (PEI) as the thermoplastic resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2002-338823 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, even with resin films containing polyether ether ketone and polyimide, the temperature required for multi-layering (hot press molding) is high, at 230°C or higher, and the heating and cooling process takes time when forming the multi-layer, which poses problems.
[0007] Therefore, in order to solve such problems of the conventional technology, the present inventors have carried out studies aimed at lowering the heat press temperature when forming a multi-layered resin film containing polyether ether ketone. [Means for solving the problem]
[0008] Examples of specific embodiments of the present invention are given below.
[0009] [1] A composition comprising polyetheretherketone and polyetherketoneketone, The glass transition temperature (Tg) is 140 to 170°C. A resin film having a difference (Tc-Tg) between its crystallization temperature (Tc) and glass transition temperature (Tg) of 50 to 70°C. [2] The resin film according to [1], further comprising polyetherimide. [3] The resin film according to [1] or [2], wherein the content of polyether ketone ketone is 1 part by mass or more and less than 50 parts by mass per 100 parts by mass of polyether ether ketone. [4] The resin film according to any one of [1] to [3], further comprising inorganic particles. [5] The resin film according to any one of [1] to [4], which has a relative crystallinity of 90% or less. [6] The resin film according to any one of [1] to [5], which has a linear expansion coefficient of 50 ppm / ° C. or less. [7] The resin film according to any one of [4] to [6], wherein the content of the inorganic particles is 10% by mass or more and less than 45% by mass based on the total mass of the resin film. [8] The resin film according to any one of [1] to [7], which has a dielectric loss tangent of 0.005 or less at a frequency of 10 GHz, a temperature of 23° C., and a relative humidity of 40%. [9] The resin film according to any one of [1] to [8], which is used for a circuit board.
[10] A circuit board material comprising the resin film according to any one of [1] to [9] and a conductor laminated thereon.
[11] A circuit board formed from the circuit board material according to
[10] .
[12] An electronic device comprising the circuit board described in
[11] . Effect of the Invention
[0010] According to the present invention, the heat press temperature can be lowered when forming a multi-layer structure using a resin film containing polyether ether ketone, thereby improving the processing and manufacturing efficiency of a multi-layer board using a resin film containing polyether ether ketone. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. The following description may be based on a representative embodiment or a specific example, but the present invention is not limited to such an embodiment. In this specification, when "X to Y" (X and Y are any numbers) is expressed, it includes "X or more and Y or less" as well as "preferably greater than X" or "preferably smaller than Y" unless otherwise specified. In addition, when "X or more" (X is any number) or "Y or less" (Y is any number) is expressed, it also includes "preferably greater than X" or "preferably less than Y". In the following description, "film" and "sheet" are not clearly distinguished from each other, and when "film" is referred to, it includes "sheet", and when "sheet" is referred to, it includes "film".
[0012] (Resin film) The present embodiment relates to a resin film (hereinafter sometimes referred to as "the present resin film") that contains polyetheretherketone and polyetherketoneketone, has a glass transition temperature (Tg) of 140 to 170°C, and has a difference (Tc-Tg) between the crystallization temperature (Tc) and the glass transition temperature (Tg) of 50 to 70°C.
[0013] Since this embodiment has the above-mentioned configuration, it is possible to multi-layer a resin film containing polyether ether ketone without using an adhesive, and the heat press temperature during multi-layering can be lowered. This makes it possible to improve the processing and manufacturing efficiency of multi-layer boards using a resin film containing polyether ether ketone. Note that, while the minimum heat press temperature during multi-layering of a conventional resin film containing polyether ether ketone was about 230°C, this embodiment makes it possible to lower the heat press temperature to about 200°C.
[0014] By multi-layering (heat pressing) the resin film of this embodiment, at least a part of the resin contained in the resin film (for example, polyether ether ketone or polyether ketone ketone described later) is crystallized. Since the resin film of this embodiment has the above-mentioned configuration, the crystallization rate of the resin in the multi-layering (heat pressing) process can be appropriately controlled, thereby improving the step-following ability of the resin film when multi-layering, and improving the adhesion between the circuit and the resin film. More specifically, in this embodiment, polyether ether ketone and polyether ketone ketone are used in combination, and further, the glass transition temperature (Tg) and Tc-Tg values of the resin film are set within a predetermined range, so that the crystallization rate of the resin in the multi-layering (heat pressing) process can be appropriately slowed. This makes it possible to suppress the shrinkage and increase in rigidity of the resin caused by the crystallization of the resin proceeding too quickly. As a result, it becomes easy to embed a circuit such as copper foil (good step-following ability), and the adhesion between the circuit and the resin film can be improved.
[0015] The glass transition temperature (Tg) of the present resin film is preferably 140°C or higher, more preferably 145°C or higher, even more preferably 150°C or higher, and particularly preferably 155°C or higher. The glass transition temperature (Tg) of the present resin film is preferably 170°C or lower. By setting the glass transition temperature (Tg) of the resin film to the above lower limit or higher, the heat resistance of the resin film can be improved. On the other hand, by setting the glass transition temperature (Tg) of the resin film to the above upper limit or lower, the resin film can be easily processed at low temperatures. For example, when used as an insulating film for a circuit board, multilayering and embedding of the circuit board at a low temperature of 200°C can be easily performed.
[0016] The crystallization temperature (Tc) of the present resin film is preferably 190°C or higher, more preferably 195°C or higher, even more preferably 200°C or higher, and particularly preferably 205°C or higher. The crystallization temperature (Tc) of the present resin film is preferably 240°C or lower. The difference (Tc-Tg) between the crystallization temperature (Tc) and the glass transition temperature (Tg) is preferably 50-70°C, more preferably 50-65°C. By setting the difference (Tc-Tg) between the crystallization temperature (Tc) and the glass transition temperature (Tg) within the above range, the crystallization rate during multi-layering (hot pressing) can be appropriately slowed down, so that the shrinkage and increase in rigidity of the resin due to the crystallization of the resin proceeding too quickly can be suppressed. As a result, it becomes easier to embed circuits such as copper foil, and the adhesion between the circuit and the resin film can be improved.
[0017] The melting point (Tm) of the present resin film is preferably 280°C or higher, more preferably 290°C or higher, and even more preferably 300°C or higher. The melting point (Tm) of the present resin film is preferably 400°C or lower, more preferably 380°C or lower, and even more preferably 360°C or lower. By setting the melting point (Tm) of the resin film to the above lower limit or higher, the heat resistance of the resin film can be improved. On the other hand, by setting the melting point (Tm) of the resin film to the above upper limit or lower, thermal deterioration of the resin due to thermal decomposition during extrusion film formation of the resin film can be suppressed.
[0018] The glass transition temperature (Tg), crystallization temperature (Tc) and melting point (Tm) of the resin film are measured using a differential scanning calorimeter Pyris1 DSC (manufactured by PerkinElmer) in accordance with JIS K7121: 2012. The temperature range during measurement is 25 to 380°C, the heating rate is 10°C / min, and the glass transition temperature is calculated from the inflection point of the DSC curve detected during the re-heating process, the melting point is calculated from the endothermic peak top temperature, and the crystallization temperature (Tc) is calculated from the exothermic peak top temperature.
[0019] The relative crystallinity of the resin film of this embodiment is preferably 90% or less, more preferably 80% or less, even more preferably 70% or less, even more preferably 50% or less, even more preferably 30% or less, and particularly preferably 20% or less. The lower limit of the relative crystallinity of the resin film is not particularly limited, but is usually 0% or more. The above relative crystallinity is a value before the resin film is subjected to heat press processing. By setting the relative crystallinity of the resin film within the above range, the molding processability (lamination processability) of the resin film can be improved. For example, by setting the relative crystallinity of the resin film within the above range, the step-following ability of the resin film when multi-layered can be improved, and as a result, it becomes easier to embed a circuit such as copper foil, and the adhesion between the circuit and the resin film can be improved. Here, the relative crystallinity of the resin film is determined by using a differential scanning calorimeter (Pyris1 DSC, manufactured by PerkinElmer) to heat a test piece obtained from the resin film at a heating rate of 10°C / min, and calculating the heat quantity (J / g) of the crystal melting peak and the heat quantity (J / g) of the recrystallization peak obtained at this time using the following formula (1). Relative crystallinity (%) = {1-(ΔHc / ΔHm)} × 100 (1) ΔHc: Heat quantity (J / g) of the recrystallization peak of the resin film when heated at 10°C / min ΔHm: Heat of crystal melting peak at 10℃ / min temperature rise of resin film (J / g) When there are multiple recrystallization peaks, the total heat quantity is calculated as ΔHc, and when there are multiple crystal melting peaks, the total heat quantity is calculated as ΔHm. When measured with a differential scanning calorimeter, a film that does not show a recrystallization peak (ΔHc = 0 J / g) can be said to be a crystallized film, and a film that shows a recrystallization peak can be said to be not completely crystallized.
[0020] The relative crystallinity of the resin film of this embodiment after multilayering (heat pressing) is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, even more preferably 85% or more, and particularly preferably 90% or more. The relative crystallinity of the resin film may be 100%. By setting the relative crystallinity of the film after multilayering (heat pressing) within the above range, it is possible to provide solder reflow heat resistance and appropriately prevent deformation of the board.
[0021] When polymeric materials crystallize, the molecular chains are regularly arranged, improving their heat resistance and mechanical properties. This is because the proportion of amorphous parts in crystallized polymeric materials is small, so the proportion of molecular chains that undergo micro-Brownian motion when heat is applied from the outside is reduced. Furthermore, when polymeric materials crystallize, the molecular chains become denser, and the intermolecular forces become stronger, making them rigid. In this resin film, the relative crystallinity before multi-layering (heat pressing) is relatively low, and the relative crystallinity after multi-layering (heat pressing) is relatively high, which improves the embedding and adhesiveness of circuits such as copper foil, while also demonstrating excellent heat resistance and mechanical properties after multi-layering (heat pressing).
[0022] The linear expansion coefficient of the resin film of this embodiment is preferably 50 ppm / °C or less, more preferably 40 ppm / °C or less, and even more preferably 35 ppm / °C or less. It is preferable that either one of the linear expansion coefficients in the MD and TD of the resin film is within the above range, but it is more preferable that both the expansion coefficients in the MD and TD are within the above range. Here, since the linear expansion coefficient of the copper foil used in circuit formation is about 20 ppm / °C (the lower limit is 15 ppm / °C or more), by setting the linear expansion coefficient of the present resin film within the above range, it is possible to approach the linear expansion coefficient of copper as much as possible. This makes it possible to suppress the inconsistency of the expansion change when the present resin film is laminated on a substrate such as copper foil, and to suppress peeling of the copper foil. The linear expansion coefficient can be calculated from the elongation of the film with respect to temperature by subjecting a test piece obtained from the resin film to a tensile test in the MD or TD direction at a constant heating rate (5°C / min) in the temperature range of 30°C to 150°C while applying a load of 1 mN using a thermomechanical analysis (TMA) device (Model: TMA / SS7100, manufactured by Hitachi High-Tech Science Corporation).
[0023] The dielectric loss tangent of the resin film at a frequency of 10 GHz, a temperature of 23°C, and a relative humidity of 40% is preferably 0.005 or less, more preferably 0.0045 or less, even more preferably 0.004 or less, even more preferably 0.0035 or less, and particularly preferably 0.003 or less. The lower limit of the dielectric loss tangent is not particularly limited, but is usually 0.001 or more. The dielectric loss tangent is an index of the electric energy loss inside the insulator, and is a value obtained from the ratio of the charging current to the lost current. In an ideal insulator, the electric energy loss is zero, so it is desirable for the dielectric loss tangent to be small. In particular, in high-frequency circuit boards, power absorption causes signal transmission loss and is converted into heat. The dielectric loss tangent affects the quality of signal transmission, and therefore, the larger the dielectric loss tangent, the greater the absorption and the greater the signal loss, and conversely, the lower the dielectric loss tangent, the less the signal loss. Furthermore, by setting the dielectric loss tangent of the resin film within the above range, the transmission efficiency of electrical signals in the circuit board can be improved, and further, higher speeds can be achieved.
[0024] The dielectric constant of the resin film at a frequency of 10 GHz, a temperature of 23° C., and a relative humidity of 40% is preferably 3.5 or less, more preferably 3.4 or less, and even more preferably 3.3 or less. The lower limit of the dielectric constant is not particularly limited, but is usually 2.0 or more. By setting the dielectric constant of the resin film within the above range, the dielectric loss is small, the transmission efficiency of the electrical signal of the circuit board is improved, and even higher speed is possible. The lower the dielectric constant, the faster the signal speed becomes, approaching the speed of light. Therefore, by using a resin film with a dielectric constant, it is possible to increase the signal speed, for example, in high-frequency circuits.
[0025] The relative dielectric constant and dielectric loss tangent of the resin film are measured in accordance with JIS C2565:1992 using a cavity resonator method under conditions of a temperature of 23° C., a relative humidity of 40%, and a frequency of 10 GHz.
[0026] The water absorption rate of the resin film is preferably 1% or less, more preferably 0.8% or less, and even more preferably 0.6% or less. The lower limit of the water absorption rate of the resin film is not particularly limited, but is usually 0.1% or more. Water absorption (water absorption rate) affects the relative dielectric constant and dielectric loss. In addition, in the present resin film, by setting the water absorption rate within the above range, peeling of the resin film from the copper foil is easily prevented. Furthermore, by setting the water absorption rate within the above range, migration resistance is improved and short circuit occurrence is easily prevented. The water absorption rate is measured by preparing a test piece from the resin film and immersing the test piece in water at 23°C for 24 hours from the change in mass before and after immersion.
[0027] When the present resin film is used as a circuit board material for electronic devices, the thickness of the present resin film is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more. The thickness of the present resin film is preferably 300 μm or less, more preferably 250 μm or less, and even more preferably 200 μm or less. The present resin film is preferably produced so that the anisotropy of the physical properties in the machine direction (MD) and the perpendicular direction (TD) is as small as possible.
[0028] <Polyetheretherketone> This resin film contains polyether ether ketone (hereinafter, sometimes referred to as "PEEK"). Polyether ether ketone has a repeating unit (a-1) represented by the following structural formula (1). The repeating unit (a-1) has two ether groups and one ketone group.
[0029] [ka]
[0030] The total number (degree of polymerization (n)) of repeating units (a-1) of PEEK is preferably 10 or more, more preferably 20 or more. The total number (degree of polymerization (n)) of repeating units (a-1) is preferably 500 or less, more preferably 100 or less. By setting the total number (degree of polymerization (n)) of repeating units (a-1) of PEEK within the above range, the crack resistance, heat resistance, and impact resistance of the resin film can be effectively improved. Furthermore, by setting the total number (degree of polymerization (n)) of repeating units (a-1) of PEEK within the above range, the increase in viscosity during melting can be suppressed, and therefore the melt moldability is also excellent.
[0031] The heat of crystalline fusion of PEEK is preferably 20 J / g or more, more preferably 25 J / g or more, and even more preferably 30 J / g or more. The heat of crystalline fusion of PEEK is preferably 60 J / g or less, more preferably 55 J / g or less, and even more preferably 50 J / g or less. By setting the heat of crystalline fusion of PEEK within the above range, the heat resistance of the resin film can be effectively improved. In addition, since only small thermal energy is required during melt molding, the melt moldability is also excellent.
[0032] The melting point of PEEK is preferably 300°C or higher, more preferably 320°C or higher, and even more preferably 340°C or higher. The melting point of PEEK is preferably 400°C or lower, more preferably 380°C or lower, and even more preferably 360°C or lower. By setting the melting point of PEEK within the above range, the heat resistance of the resin film can be effectively improved. Furthermore, by setting the melting point of PEEK within the above range, resin deterioration due to thermal decomposition during melt molding can also be suppressed.
[0033] The glass transition temperature of PEEK is preferably 120°C or higher, more preferably 140°C or higher. The glass transition temperature of PEEK is preferably 200°C or lower, more preferably 180°C or lower. By setting the glass transition temperature of PEEK within the above range, the heat resistance of the resin film can be effectively improved. In addition, since the increase in viscosity during melting can be suppressed, the melt moldability is also excellent.
[0034] The glass transition temperature, heat of crystalline fusion, and melting point of PEEK are determined from DSC (Differential Scanning Calorimetry) curves detected when the material is heated at a temperature range of 25 to 400°C and a heating rate of 10°C / min using a differential scanning calorimeter in accordance with JIS K 7121:2012 and JIS K 7122:2012.
[0035] The melt volume rate (MVR) of PEEK is preferably 1 or more, more preferably 5 or more, and particularly preferably 10 or more. The MVR of PEEK is preferably 100 or less, more preferably 80 or less, and particularly preferably 50 or less. By setting the MVR of PEEK within the above range, the film formability and film strength of the resin film can be improved. The MVR is measured in accordance with ISO 1133 and is determined by measuring at 380°C and 5 kgf.
[0036] PEEK can be produced by known methods, and commercially available products can also be used, such as the "VICTREX PEEK" series manufactured by Victrex, the "KetaSpire" series manufactured by Solvay, and the "VESTAKEEP" series manufactured by Daicel-Evonik.
[0037] <Polyetherketoneketone> This resin film contains polyetherketoneketone (hereinafter, sometimes referred to as "PEKK"). PEKK is a thermoplastic resin that has a high tensile modulus and a suitable heat of crystalline fusion from the viewpoint of moldability. In this embodiment, by containing PEKK in addition to PEEK, the glass transition temperature (Tg) can be lowered while keeping the difference (Tc-Tg) between the crystallization temperature (Tc) and the glass transition temperature (Tg) of the resin film within a desired range, and therefore the heat press temperature during multi-layering can be lowered.
[0038] PEKK preferably has a repeating unit (b-1) represented by the following structural formula (2) and a repeating unit (b-2) represented by the following structural formula (3). That is, it is preferable to have two types of repeating units. Both repeating units (b-1) and (b-2) have one ether group and two ketone groups.
[0039] [ka]
[0040] [ka]
[0041] The content ratio of the repeating units (b-1) and (b-2) in PEKK ((b-1):(b-2) (mol%)) is not particularly limited, but is preferably 55:45 to 75:25, more preferably 58:42 to 73:27, and even more preferably 60:40 to 70:30. Here, the molar content ratio of the repeating units (b-1) and (b-2) in PEKK can be measured, for example, using NMR. When the molar ratio of (b-1) is 55% or more, the glass transition temperature (Tg) of the resin film can be easily adjusted to a desired range, and excellent heat resistance can be easily exhibited. On the other hand, when the molar ratio of (b-1) is 75% or less, the crystallization speed during multi-layering is slowed down, making it easier to embed circuits such as copper foil, and making it easier to improve the adhesion between the circuit and the resin film.
[0042] As described above, the PEKK having the repeating units (b-1) and (b-2) may be used alone or in combination of two or more. When two or more types of PEKK are used in combination, those having different contents of the repeating units (b-1) and (b-2) may be used in combination.
[0043] The total number of repeating units (b-1) and (b-2) (degree of polymerization (n)) is preferably 10-100, and more preferably 20-50, from the viewpoint of ensuring mechanical properties.
[0044] The glass transition temperature of PEKK is preferably 140°C or higher, more preferably 145°C or higher, and even more preferably 150°C or higher. The glass transition temperature of PEKK is preferably 200°C or lower, more preferably 190°C or lower, even more preferably 180°C or lower, and particularly preferably 170°C or lower. If the glass transition temperature is equal to or higher than the lower limit, a resin film having sufficient heat resistance is easily obtained. If the glass transition temperature is equal to or lower than the upper limit, molding processability at low temperatures is easily obtained.
[0045] PEKK may or may not have a melting point, and if it does have a melting point, it is preferably 250°C or higher, more preferably 270°C or higher, and even more preferably 300°C or higher. The melting point of PEKK is preferably 400°C or lower, more preferably 380°C or lower, and even more preferably 360°C or lower. By setting the melting point of PEKK within the above range, the heat resistance of the resin film can be effectively improved. Furthermore, by setting the melting point of PEKK within the above range, resin deterioration due to thermal decomposition during melt molding can also be suppressed.
[0046] The heat of crystalline fusion of PEKK is preferably 60 J / g or less, more preferably 40 J / g or less, even more preferably 20 J / g or less, and may be 0 J / g. If the heat of crystalline fusion of PEKK is equal to or less than the upper limit mentioned above, shrinkage of the resin film is easily suppressed when crystallized during multi-layering (heat pressing).
[0047] The glass transition temperature and heat of crystalline fusion of PEKK are determined from DSC (Differential Scanning Calorimetry) curves detected when the material is heated in the temperature range of 25 to 400°C at a heating rate of 10°C / min using a differential scanning calorimetry (DSC) in accordance with JIS K 7121:2012 and JIS K 7122:2012.
[0048] The content of polyether ketone ketone (PEKK) is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, relative to 100 parts by mass of polyether ether ketone (PEEK). The content of polyether ketone ketone (PEKK) is preferably less than 50 parts by mass, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less. By setting the content of PEKK relative to PEEK within the above range, it becomes easier to lower the heat press temperature during multi-layering to a relatively low temperature (for example, about 200°C). In addition, by setting the content of PEKK relative to PEEK within the above range, the crystallization speed of the resin in the multi-layering (heat press) process can be appropriately slowed down, making it easier to embed circuits such as copper foil, and the adhesion between the circuit and the resin film can be more effectively improved.
[0049] The melt volume rate (MVR) of PEKK is preferably 1 or more, more preferably 5 or more, and particularly preferably 10 or more. The MVR of PEKK is preferably 100 or less, more preferably 80 or less, and particularly preferably 50 or less. By setting the MVR of PEKK within the above range, the film formability and film strength of the resin film can be improved. The MVR is measured in accordance with ISO 1133 and is determined by measuring at 380°C and 5 kgf.
[0050] PEKK can be produced by known methods (see, for example, JP-A-61-195122 and JP-A-62-129313). Commercially available products can also be used. Examples include the "KEPSTAN" series manufactured by Arkema, the "Kstone" series manufactured by Shandong Kaishen New Materials Co., Ltd., and "NovaSpire" manufactured by Solvay.
[0051] <Polyetherimide> The resin film preferably further contains polyetherimide (hereinafter, sometimes referred to as "PEI"). PEI has an imide group and is amorphous, so it can improve adhesion to circuits such as copper foil. There are no particular limitations on the polyetherimide, and its manufacturing method and characteristics are described in, for example, U.S. Patent 3,905,942 and U.S. Patent 3,803,085.
[0052] Since PEI and PEEK are mutually compatible resins, the crystallinity (heat of crystal fusion) of PEEK can be adjusted by using PEEK and PEI in combination. In addition, by using PEEK and PEI in combination, the crystallization rate of PEEK can be adjusted and the glass transition temperature when the resin composition is in an amorphous state can be increased (Tg of PEEK is 143°C, while Tg of PEI is 217°C). Since PEI is an amorphous resin, the melting point of the resin itself does not change even when PEEK and PEI are combined, and heat resistance is maintained. In this embodiment, PEKK is further used in combination with PEEK and PEI, so that the difference (Tc-Tg) between the glass transition temperature, crystallization temperature (Tc), and glass transition temperature (Tg) of the resin film can be set to a desired range. PEKK and PEI are mutually compatible resins, while PEKK and PEEK are incompatible resins, so that it is possible to adjust thermal characteristic parameters (glass transition temperature and crystallization temperature). In this embodiment, by setting the difference (Tc-Tg) between the glass transition temperature, crystallization temperature (Tc) and glass transition temperature (Tg) of the resin film within a desired range, the heat press temperature when the resin film is multi-layered can be reduced, and the processing and manufacturing efficiency of multilayer boards using the resin film can be more effectively improved. In this embodiment, the resin is not limited to PEI, and other resins may be used as long as they are compatible with PEEK and PEKK.
[0053] PEI is an amorphous resin, and specifically, it is preferable that it has a repeating unit represented by the following structural formula (4). It is preferable that polyetherimide has the following repeating unit structure, since it is easy to improve various performances. The amorphousness of a polyetherimide resin can be determined by DSC.
[0054] [ka]
[0055] In formula (4), Y 1 ~Y 6 each independently represents a hydrogen atom, an alkyl group, or an alkoxy group; Ar 7 ~Ar 9 each independently represents an arylene group having 6 to 24 carbon atoms which may have a substituent; X 1 is a single bond, or -O-, -SO 2 It represents any one of -, -S-, -C(=O)-, or a divalent aliphatic hydrocarbon group.
[0056] The polyetherimide preferably has a structure in which the repeating unit represented by the above formula (4) is repeated, for example, 10 to 1000 times, and the number of repeating units (n) is more preferably 20 to 700, and further preferably 30 to 500. If the number of repeating units is within the above range, the viscosity when melted is not too high, and the moldability is excellent, and various properties such as heat resistance and heat aging resistance tend to be well-balanced.
[0057] Y 1 ~Y 6 The alkyl group in the formula (I) is, for example, an alkyl group having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms, and further preferably 1 to 2 carbon atoms. Specific preferred examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a 1-methylpentyl group, an n-hexyl group, and an isohexyl group. Also, Y 1 ~Y 6 The alkoxy group in the formula (I) is, for example, an alkoxy group having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms, and even more preferably 1 to 2 carbon atoms. Specifically preferred examples include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, a sec-butoxy group, a tert-butoxy group, an n-pentyloxy group, and an n-hexyloxy group. Y 1 ~Y 6 may be the same or different. 1 ~Y 6 At least one of Y is preferably a hydrogen atom. 1 ~Y 6 It is more preferable that all of are hydrogen atoms.
[0058] Ar 7 ~Ar 9 Examples of the arylene group in the formula include a phenylene group, a naphthylene group, and an anthracenylene group. Examples of the substituent of the arylene group include an alkyl group, a halogen, an alkoxy group, a halogen-substituted alkyl group, etc. The alkyl group and alkoxy group as the substituent have, for example, 1 to 6 carbon atoms, preferably 1 to 2 carbon atoms, and specific examples thereof are as described above. A halogen-substituted alkyl group is an alkyl group in which one or more hydrogen atoms are substituted with halogen. The alkyl group in the halogen-substituted alkyl group is the same as described above. Examples of halogen include a chlorine atom, a bromine atom, a fluorine atom, and an iodine atom. 7 ~Ar 9 may be the same or different. Ar 7 ~Ar 9 When Ar has a substituent, the number of carbon atoms in the arylene group is preferably 6 to 24. 7 ~Ar 9 is preferably a phenylene group which may have a substituent, and of these, a phenylene group is preferable.
[0059] X 1 The divalent aliphatic hydrocarbon group in is preferably a divalent aliphatic hydrocarbon group having 1 to 6 carbon atoms, and more preferably a divalent saturated aliphatic hydrocarbon group having 1 to 6 carbon atoms. y H 2y - (y is an integer of 1 to 6), specifically, a methylene group, a dimethylene group, a trimethylene group, a propylene group, an ethylidene group (-CH(CH 3 )-), dimethylmethylene group (-C(CH 3 ) 2 -) and others. X 1 is preferably a divalent saturated aliphatic hydrocarbon group, and particularly preferably a dimethylmethylene group (-C(CH 3 ) 2 -) is more preferable.
[0060] In the above formula (4), Ar 9 may be a 1,4- or 1,3-arylene group having 6 to 24 carbon atoms which may have a substituent, and is preferably a 1,4-arylene group having 6 to 24 carbon atoms which may have a substituent. By bonding to the imide group at the 1- and 4-positions, the structure is stable and heat aging resistance is improved, and excellent low water absorption, heat resistance, and impact resistance such as puncture impact strength tend to be easily achieved. Therefore, it is preferable that the polyetherimide has a repeating unit represented by the following structural formula (5):
[0061] [ka]
[0062] In formula (5), Y 1 ~Y 6 each independently represents a hydrogen atom, an alkyl group, or an alkoxy group; Ar 7 ~Ar 9 each independently represents an arylene group having 6 to 24 carbon atoms which may have a substituent; X 1 is a single bond, or -O-, -SO 2(1,4)Ar in formula (5) represents either -, -S-, -C(=O)-, or a divalent aliphatic hydrocarbon group. 9 The imide group is Ar 9 This indicates that the aryl group is bonded to the 1st and 4th positions.
[0063] Y in Equation (5) 1 ~Y 6 , X 1 is as explained above. Ar 9 The arylene group in may be a 1,4-phenylene group, a 1,4-naphthylene group, a 1,4-anthracenylene group, etc. These arylene groups may have a substituent as described above, and the substituent is as described above. 9 is preferably a 1,4-phenylene group which may have a substituent, and more preferably a 1,4-phenylene group.
[0064] In formula (5), Ar 7 , Ar 8 is as explained above, but Ar 7 and Ar 8 is preferably a 1,4-arylene group having 6 to 24 carbon atoms which may have a substituent, and examples of the 1,4-arylene group include a 1,4-phenylene group, a 1,4-naphthylene group, and a 1,4-anthracenylene group. These arylene groups may have a substituent as described above, and the substituent is as described above. Ar 7 and Ar 8 is more preferably a 1,4-phenylene group which may have a substituent, and further preferably a 1,4-phenylene group.
[0065] Among them, it is particularly preferable that the polyetherimide used in the present resin film has a repeating unit represented by the following structural formula (6). When the polyetherimide has the following structure, the present resin film is likely to have excellent mechanical properties, and also tends to have excellent crystallinity, heat resistance, and good adhesion to metals, etc. Furthermore, the moldability and secondary processability are also likely to be good.
[0066] [ka]
[0067] In formula (6), the number of repeating units (n) is preferably 10 to 1000, more preferably 20 to 700, and even more preferably 30 to 500. When the number of repeating units (n) is within the above range, the viscosity when melted is not too high, and moldability is excellent, and the balance of various properties such as heat resistance and heat aging resistance tends to be excellent.
[0068] More specifically, it is particularly preferable that the polyetherimide has a repeating unit represented by the following structural formula (7) or (8). In the formulas (7) and (8), the number of repeating units (n) is preferably 10 to 1000, more preferably 20 to 700, and even more preferably 30 to 500. When the number of repeating units (n) is within the above range, the viscosity when melted is not too high, and the moldability is excellent, and the balance of various properties such as heat resistance and heat aging resistance tends to be excellent. [ka]
[0069] The polyetherimide resin having the structure represented by the above structural formula (7) is a polycondensate (meta-polyetherimide) of 4,4'-[isopropylidenebis(p-phenyleneoxy)]diphthalic dianhydride and m-phenylenediamine, and is compatible with polyarylketone resins, such as PEEK. The polyetherimide resin having the structure represented by the structural formula (8) is a polycondensate (para-polyetherimide) of 4,4'-[isopropylidenebis(p-phenyleneoxy)]diphthalic dianhydride and p-phenylenediamine, and is partially compatible with polyarylketone resins, such as PEEK. In this embodiment, it is preferable to use the PEI represented by the structural formula (7) since the crystallization rate of PEEK can be further slowed by using the PEI represented by the structural formula (7). On the other hand, the crystallization rate of PEEK can also be slowed by using the PEI represented by the structural formula (8).
[0070] The glass transition temperature of PEI is preferably 160°C or higher, more preferably 170°C or higher, even more preferably 180°C or higher, even more preferably 190°C or higher, and particularly preferably 200°C or higher. The glass transition temperature of PEI is preferably 300°C or lower, more preferably 290°C or lower, even more preferably 280°C or lower, even more preferably 270°C or lower, and particularly preferably 260°C or lower. If the glass transition temperature is the above lower limit or higher, a resin film having sufficient heat resistance is easily obtained. If the glass transition temperature is the above upper limit or lower, molding processability at low temperatures is easily obtained.
[0071] The melt volume rate (MVR) of PEI is preferably 1 or more, more preferably 5 or more, and particularly preferably 10 or more. The MVR of PEI is preferably 100 or less, more preferably 80 or less, and particularly preferably 50 or less. By setting the MVR of PEI within the above range, the film formability and film strength of the resin film can be improved. The MVR is measured according to ISO 1133 and is determined by measuring at 380°C and 5 kgf.
[0072] The content of polyetherimide (PEI) is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of polyetheretherketone (PEEK). The content of polyetherimide (PEI) is preferably less than 80 parts by mass, more preferably 70 parts by mass or less, and even more preferably 60 parts by mass or less. By setting the content of PEI relative to PEEK within the above range, the Tc-Tg value of the resin film can be adjusted to an appropriate value, and the crystallization rate of the resin in the multilayering (heat pressing) process can be appropriately slowed, making it easier to embed circuits such as copper foil, and the adhesion between the circuit and the resin film can be more effectively improved. In addition, the increase in Tg of the resin film can be suppressed, and the value of the dielectric tangent can be reduced.
[0073] As the PEI, for example, those commercially available under the trade name "Ultem" series from Savic Innovative Plastics can be used.
[0074] <Inorganic particles> The present resin film may contain inorganic particles. By further containing inorganic particles, the film formability and appearance of the resin film can be improved, and further the dielectric properties and dimensional stability of the resin film can be improved.
[0075] The inorganic particles are not particularly limited, and various kinds can be mentioned. Specifically, for example, spherical, fibrous, needle-like, scaly, plate-like or flaky (flat) powders made of inorganic substances such as mica, clay, glass, silica, aluminum nitride, silicon nitride, boehmite, talc, kaolin, sericite, illite, kaolinite, montmorillonite, vermiculite, smectite, alumina, titanates such as magnesium potassium titanate and lithium potassium titanate, calcium carbonate, etc. can be mentioned. Among them, the inorganic particles are preferably at least one selected from the group consisting of mica, silica, glass, talc, kaolin and calcium carbonate. In addition, the inorganic particles are preferably fluorine-containing inorganic particles containing fluorine, more preferably fluorine-containing mica (fluorine mica), and particularly preferably fluorine phlogopite. By using fluorine-containing inorganic particles containing fluorine as the inorganic particles, the dielectric properties of the resin film can be improved.
[0076] Mica is a plate-like crystal belonging to the mica family of phyllosilicate minerals, and is classified into two types: natural mica (muscovite, biotite, phlogopite, etc.) and synthetic mica that is artificially produced. In particular, synthetic mica is known in which the hydroxyl groups (OH) of naturally occurring mica are replaced with fluorine (F) to enable use at high temperatures. Synthetic mica is known to be synthesized by hydrothermal synthesis, solid-phase synthesis, melting, etc., and any method may be used, but it is preferably synthesized by a melting method in which 100% of the hydroxyl groups are replaced with fluorine.
[0077] Among the synthetic mica particles, it is particularly preferable to use non-swelling synthetic mica from the viewpoint of heat dimensional stability and water resistance. As the non-swelling synthetic mica, for example, fluorine phlogopite (K 2 Mg 6 Al 2 (Si 6 O 20 )F 4 ), potassium tetrasilicic mica (K 2 Mg 5 (Si 8 O 20)F 4 ), potassium teniolite (K 2 Mg 4 Li 2 (Si 8 O 20 )F 4 Among them, it is particularly preferable to use fluorine-containing mica, which can further reduce the dielectric tangent of the resin film.
[0078] Examples of synthetic mica include the "PDM" series manufactured by Topy Industries, the "MK" series manufactured by Katakura Coop Agri, and the "NK" and "NS" series manufactured by Nihon Kohken Kogyo.
[0079] The median diameter (D50) of the inorganic particles is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more. The median diameter (D50) of the inorganic particles is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. By setting the median diameter (D50) of the inorganic particles within the above range, the dielectric tangent and linear expansion coefficient of the resin film can be more effectively reduced. The median diameter (D50) of the inorganic particles is measured using a laser diffraction particle size distribution measuring device, and the particle diameter at which the cumulative number from the small particle diameter side is 50% is taken as D50.
[0080] When the inorganic particles in the film are plate-like or scaly, the aspect ratio of the inorganic particles is preferably from 2 to 20, more preferably from 2.2 to 15, even more preferably from 2.5 to 10, even more preferably from 2.7 to 8, and particularly preferably from 3 to 5. Inorganic particles with an aspect ratio within such ranges not only can prevent defects such as holes from occurring in the film, but also have good dispersibility with little aggregation, so that the inorganic particles can be highly loaded into the film while maintaining the film-forming properties and mechanical properties, and the film can have a low linear expansion coefficient.
[0081] The aspect ratio of inorganic particles (=long axis diameter / short axis diameter) can be obtained by observing inorganic particles in the cross section of the film in the film width direction (TD, direction perpendicular to the flow direction) with an electron microscope, determining the long axis diameter (maximum diameter) and short axis diameter (diameter perpendicular to the maximum diameter) of each inorganic particle, and then calculating the aspect ratio of each inorganic particle. At this time, at least 100 or more inorganic particles are arbitrarily selected, the aspect ratio of each inorganic particle is calculated, and the average is taken as the average aspect ratio. In addition, when the inorganic particles are scaly, the average value of the diameter of each inorganic particle, i.e., the diameter of the long axis is taken as the diameter, is taken as the average value of the thickness of each inorganic particle.
[0082] The content of the inorganic particles is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, based on the total mass of the resin film. The content of the inorganic particles is preferably less than 45% by mass, more preferably 40% by mass or less, and even more preferably 35% by mass or less, based on the total mass of the resin film. By setting the content of the inorganic particles within the above range, the film formability and appearance of the resin film can be improved, and furthermore, the effect of reducing the linear expansion coefficient of the resin film can be expected.
[0083] <Optional ingredients> In addition to the above-mentioned components, the resin film may contain other resins, fillers, and various additives, as necessary, such as heat stabilizers, ultraviolet absorbers, light stabilizers, nucleating agents, colorants, lubricants, and flame retardants.
[0084] In this embodiment, a nucleating agent may be added to increase the relative crystallinity of the resin film. The addition of the nucleating agent promotes the generation of crystal nuclei and improves the crystal density, so that the relative crystallinity after multi-layering can be effectively increased. There are no particular limitations on the nucleating agent as long as it is one that is generally used as a nucleating agent for thermoplastic resins.
[0085] <Method of manufacturing the resin film> The resin film can be produced, for example, by melt-kneading materials such as PEEK and PEKK, followed by quenching to form a film. In the present embodiment, it is preferable to produce the resin film by melt-kneading, for example, PEEK, PEKK, PEI, and inorganic particles, followed by quenching to form a film.
[0086] Examples of methods for producing a resin film include inflation molding, extrusion cast molding using a T-die, and calendar molding. Among these, extrusion cast molding using a T-die is preferred from the viewpoints of film formability and stable productivity. Films may also be produced by press molding.
[0087] The molding temperature in the extrusion cast molding method using a T-die is appropriately adjusted depending on the flow characteristics and film-forming properties of the composition, but is generally from the melting point to 430° C. The thickness of the resin film is not particularly limited, but is usually about 10 to 300 μm.
[0088] For melt kneading, commonly used single screw extruders, twin screw extruders, kneaders, mixers, etc. can be used, and are not particularly limited. The rotation speed of the extruder or mixer varies depending on the shape and size of the screw used, but is preferably 10 rpm or more from the viewpoint of dispersing the inorganic particles, and is particularly preferably 15 rpm or more. There is no particular upper limit to the rotation speed, but it is preferably less than 100 rpm from the viewpoint of suppressing pulverization of the inorganic particles and suppressing decomposition of the resin due to shear heat.
[0089] As mentioned above, the relative crystallinity of the resin film is preferably 90% or less. The relative crystallinity of the resin film can be adjusted by appropriately adjusting the type of resin used. In the case of the extrusion casting method using a T-die, a film with a low relative crystallinity can be obtained by quenching the film extruded from the T-die.
[0090] As a method for adjusting the cooling conditions when cooling the molten material to form a film, for example, a cast roll is used as a cooling machine and the extruded molten resin is brought into contact with the cast roll.
[0091] When a resin film is formed by press molding, for example, a molten and mixed material is poured between two metal plates, and press molded under conditions of a temperature of 330°C to 380°C, a pressure of 2 MPa to 10 MPa, and a molding time of 10 seconds to 60 seconds, and then quenched with water to 200°C or less to form a film.
[0092] <Applications of resin film> Examples of applications of the present resin film include, but are not limited to, copper foil laminates, flexible printed circuit boards, multilayer printed wiring boards, circuit boards for electric and electronic devices such as capacitors, underfill materials, interchip fills for 3D-LSI, insulating sheets, and heat dissipation substrates. Among these, the present resin film is preferably used for circuit boards for electric and electronic devices. That is, the present resin film is preferably a resin film for forming a circuit board.
[0093] The present embodiment may relate to a rolled body obtained by rolling up a resin film. Since the resin film has appropriate strength and flexibility, it can be stored or distributed in the form of a roll.
[0094] <Circuit board material / circuit board> A circuit board material according to one example of this embodiment is formed by laminating the above-mentioned present resin film and a conductor. A circuit can be formed from the conductor to constitute a circuit board. This embodiment may also relate to a wound body formed by winding the circuit board material.
[0095] An example of the conductor is copper foil. In a circuit board, the copper foil can be patterned into a predetermined shape by etching or the like to form wiring or the like. The thickness of the copper foil before patterning is, for example, preferably 1 μm or more and 80 μm or less, more preferably 3 μm or more and 50 μm or less, and even more preferably 5 μm or more and 30 μm or less.
[0096] In the circuit board material of this embodiment, when a conductor (copper foil) is laminated, it is preferable that it is directly laminated on the resin film without an adhesive layer. Then, after the copper foil is laminated on the resin film to form the circuit board material, the copper foil is patterned into a predetermined shape. Thereafter, a conductive paste is applied as necessary, and a circuit board can be formed by laminating a plurality of these and performing a batch multi-layer press process. In this way, in this embodiment, the circuit board can be formed without using an adhesive layer. Therefore, the circuit board can be made thin, and it is easy to exhibit excellent heat resistance and mechanical properties. In addition, since the circuit board does not have an adhesive layer, the dielectric tangent and linear expansion coefficient can be more effectively reduced. The manufacturing method of the circuit board is not limited to the above.
[0097] The copper foil may be subjected to a surface treatment. For example, the copper foil surface may be treated with a surface treatment agent such as a silane coupling agent. The copper foil may be bonded to the base film via the surface treatment agent.
[0098] When forming a circuit board, a resin film having a patterned copper foil is multi-layered. When multi-layering, it is preferable to perform heat press processing. The heat press temperature is preferably 300°C or less, more preferably 280°C or less, further preferably 260°C or less, and particularly preferably 240°C or less. In addition, the heat press temperature is preferably 180°C or more. In this embodiment, the resin film can be multi-layered by heat press processing at a low temperature of about 200°C.
[0099] The resin film may be one of a base film and a cover film in a circuit board. The base film is a substrate of the circuit board, and copper foil may be provided on the base film. The cover film is sometimes called a coverlay film, and is a film for covering and protecting the copper foil provided on the base film. The cover film is used by being attached to the surface of the base film or rigid board, which is a substrate of the circuit board, on which the copper foil is provided. The cover film may generally be attached directly to the substrate, such as the base film or rigid board, or may be attached via an adhesive layer.
[0100] Copper foil is generally patterned and provided partially on a base film, but in the parts of the base film where the copper foil is not provided, the cover film may be directly adhered to the base film or may be attached to the substrate via an adhesive layer.
[0101] The circuit board according to this embodiment is made of the above-mentioned circuit board material and has at least the above-mentioned resin film and a patterned conductor (copper foil). The circuit board may be a high-frequency circuit board, and specific examples of its use include FPC (Flexible Printed Circuits) and FCCL (Flexible Cupper Clad Laminate).
[0102] <Electronic equipment> The present embodiment relates to an electronic device including the circuit board described above. Examples of the electronic device include mobile electronic devices such as mobile phones, smartphones (mobile phones), electronic organizers, digital still cameras, and video cameras, electronic paper, televisions, DVD players, various audio devices, car navigation devices, in-vehicle displays such as instrument panels, calculators, printers, scanners, copiers, refrigerators, and washing machines. EXAMPLES
[0103] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0104] <Measurement and Evaluation> (1) Glass transition temperature (Tg), crystallization temperature (Tc), melting point (Tm) and relative crystallinity The resin film was measured in accordance with JIS K7121:2012 using a differential scanning calorimeter Pyris1 DSC (manufactured by PerkinElmer) at a temperature range of 25 to 380°C and a heating rate of 10°C / min. The glass transition temperature was determined from the inflection point of the DSC curve detected during the re-heating process, the melting point was determined from the endothermic peak top temperature, and the crystallization temperature (Tc) was determined from the exothermic peak top temperature. The relative crystallinity of the film was calculated according to the following formula. Relative crystallinity (%) = {(|ΔHm|-|ΔHc|) / ΔHm} × 100 Here, ΔHc is the heat of crystallization, and ΔHm is the heat of crystal fusion.
[0105] (2) Dielectric constant The resin film was measured using a cavity resonator method in accordance with JIS C2565:1992 under conditions of a temperature of 23° C., a relative humidity of 40%, and a frequency of 10 GHz.
[0106] (3) Dielectric tangent The resin film was measured using a cavity resonator method in accordance with JIS C2565:1992 under conditions of a temperature of 23° C., a relative humidity of 40%, and a frequency of 10 GHz.
[0107] (4) Linear expansion coefficient The resin film was cut to a size of 4 mm x 10 mm, and a tensile test was performed in the MD or TD direction using a thermomechanical analysis (TMA) device (Hitachi High-Tech Science Corporation, model: TMA / SS7100) at a constant heating rate (5°C / min) in the temperature range of 30°C to 150°C while applying a load of 1 mN. The coefficient of linear expansion (CTE) was measured from the elongation of the film with respect to temperature.
[0108] (5) 200℃ Lamination Evaluation Five resin films measuring 100 mm x 100 mm were stacked together, then sandwiched between two metal plates and hot pressed at a temperature of 200°C, pressure of 3 MPa, and time of 20 minutes to obtain a laminate. The resulting laminate was allowed to absorb moisture using a pressure cooker tester at a temperature of 121°C, pressure of 2 atm, relative humidity of 100%, and time of 2 hours. It was then immersed in a solder bath at 240°C for 20 seconds to evaluate deformation. In this example, samples that showed no change in appearance after immersion in the solder bath were rated as A, samples that showed no voids after immersion in the solder bath but had not been sufficiently crystallized, causing the film to shrink, were rated as B, and samples that showed insufficient adhesion between films after immersion in the solder bath and caused voids were rated as C.
[0109] <Raw materials> [Polyetheretherketone (A)] (A)-1: VESTAKEEP 3300G (manufactured by Daicel Evonik, Tg = 145 ° C, Tm = 338 ° C, MVR (380 ° C, 5 kgf) = 20 cm 3 / 10min)
[0110] [Polyetherketoneketone (B)] (B)-1: KEPSTAN6002 (manufactured by Arkema, (b-1):(b-2)=60:40(mol%), Tg=153℃, Tm=306℃, MVR (380℃, 5kgf)=35cm 3 / 10min) (B)-2: KEPSTAN7002 (manufactured by Arkema, (b-1):(b-2)=70:30(mol%), Tg=158℃, Tm=331℃, MVR (380℃, 5kgf)=35cm3 / 10min) Here, Tg indicates the glass transition temperature, and Tm indicates the melting point.
[0111] [Polyetherimide (C)] (C)-1:Ultem 1000-1000 (structural formula (7), manufactured by Sabic, Tg=213℃, MVR (380℃, 5kgf)=13cm 3 / 10min) (C)-2: Ultem CRS5001-1000 (structural formula (8), manufactured by Sabic, Tg=225℃, MVR (380℃, 5kgf)=7cm 3 / 10min)
[0112] [Inorganic particles (D)] (D)-1: Fluorine-containing mica (Topy Industries PDM-5L (flat shape), particle size (D50) at 50% cumulative number from the small particle size side is 6.4 μm when measured with a laser diffraction particle size distribution analyzer)
[0113] Example 1 A mixed composition obtained by mixing (A)-1, (B)-1, (C)-1, and (D)-1 as shown in Table 1 was kneaded at 380°C using a Φ40 mm co-rotating single screw extruder equipped with a T-die, extruded from the T-die, and then cooled with a casting roll at about 150°C to produce a resin film with a thickness of 50 μm. The relative crystallinity of the obtained resin film was 0%.
[0114] Example 2 A resin film was produced in the same manner as in Example 1, except that the mixing mass ratio of (A)-1, (B)-1, (C)-1 and (D)-1 was changed as shown in Table 1. The relative crystallinity of the obtained resin film was 0%.
[0115] Example 3 Except for using (B)-2 instead of (B)-1, a resin film was produced in the same manner as in Example 1. The relative crystallinity of the obtained resin film was 0%.
[0116] Comparative Example 1 A mixed composition obtained by mixing (A)-1, (C)-1, (C)-2 and (D)-1 as shown in Table 1 was kneaded at 380°C using a Φ40mm co-rotating single screw extruder equipped with a T-die, extruded from the T-die and then cooled with a casting roll at about 150°C to produce a resin film with a thickness of 50μm. The relative crystallinity of the obtained resin film was 0%.
[0117] (Comparative Examples 2 and 3) A mixed composition obtained by mixing (A)-1, (B)-1, and (D)-1 as shown in Table 1 was kneaded at 380°C using a Φ40 mm co-rotating single screw extruder equipped with a T-die, extruded from the T-die, and then cooled with a casting roll at about 150°C to produce a resin film with a thickness of 50 μm. The relative crystallinity of the obtained resin film was 0%.
[0118] Comparative Example 4 A mixed composition obtained by mixing (A)-1 and (D)-1 as shown in Table 1 was kneaded at 380°C using a Φ40 mm co-rotating single screw extruder equipped with a T-die, extruded from the T-die, and then cooled with a casting roll at about 150°C to produce a resin film with a thickness of 50 μm. The relative crystallinity of the obtained resin film was 20%.
[0119] [Table 1]
[0120] The resin films obtained in the examples could be laminated at low temperatures without using an adhesive. In addition, the resin films obtained in the examples tended to have low dielectric tangents and low linear expansion coefficients. On the other hand, in the comparative examples, when laminated at 200°C, deformation due to insufficient crystallization and voids due to insufficient adhesion between films caused by a fast crystallization rate were observed, and lamination at low temperatures (200°C) was not possible.
Claims
1. Polyetheretherketone and polyetherketoneketone, The glass transition temperature (Tg) is 140 to 170° C. A resin film having a difference (Tc-Tg) between its crystallization temperature (Tc) and glass transition temperature (Tg) of 50 to 70°C.
2. The resin film according to claim 1 , further comprising a polyetherimide.
3. The resin film according to claim 1 , wherein the content of the polyether ketone ketone is 1 part by mass or more and less than 50 parts by mass with respect to 100 parts by mass of the polyether ether ketone.
4. The resin film according to claim 1 , further comprising inorganic particles.
5. The resin film according to claim 1 , having a relative crystallinity of 90% or less.
6. The resin film according to claim 1 , which has a linear expansion coefficient of 50 ppm / ° C. or less.
7. The resin film according to claim 4 , wherein the content of the inorganic particles is 10% by mass or more and less than 45% by mass with respect to the total mass of the resin film.
8. The resin film according to claim 1, which has a dielectric loss tangent of 0.005 or less at a frequency of 10 GHz, a temperature of 23° C. and a relative humidity of 40%.
9. The resin film according to claim 1 , which is used for a circuit board.
10. A circuit board material comprising the resin film according to any one of claims 1 to 9 laminated with a conductor.
11. A circuit board formed from the circuit board material of claim 10.
12. An electronic device comprising the circuit board according to claim 11.
Citation Information
Patent Citations
Heat-resistant film for substrate and printed wiring board obtained using the same
JP2002338823A